Penerapan Pendekatan Problem Based Learning Pada Mata Pelajaran Pendidikan Pokok Bahasan Macam-Macam Sujud Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas VIII F SMP Negeri 1 Ngawen Kecamatan Ngawen Kabupaten Blora Tahun 2021/2022 - Zubaidi (Jurnal Studi Islam dan Sosial, 2020)
This writing uses the Class Action Writing method which is carried out in class VIIIF of SMP Negeri 1 Ngawen, Ngawen District, Blora Regency through two cycles. In cycle I, cycle and cycle II. Data collection techniques were carried out by giving tests, observations and giving questionnaires. Tests are used to measure learning outcomes, while questionnaires are used to measure learning motivation, and observation sheets are used to observe teachers in the learning process by applying a problem based learning approach and to determine student motivation in teaching and learning activities. increased motivation and student learning outcomes. In the first cycle, the aspect of learning motivation with a good category was only the aspect of feeling happy. In the second cycle, all aspects of learning motivation are in good category. And student learning outcomes also increase with the minimum completeness criteria that have been set, namely 70. Of the 36 students, before the writing was held 10 students completed with a percentage of 28%, in the first cycle students completed learning with a percentage of 19 children with a percentage of 53%, in the second cycle students completed learning with a percentage of 32 children with a percentage of 94%. Thus, it can be concluded that the application of the problem based learning approach can increase the motivation and learning outcomes of class VIIIF students of SMP Negeri 1 Ngawen, Ngawen District, Blora Regency for the 2021/2022 Academic Year.